2012
DOI: 10.1104/pp.112.195370
|View full text |Cite
|
Sign up to set email alerts
|

Paxillus involutus Strains MAJ and NAU Mediate K+/Na+ Homeostasis in Ectomycorrhizal Populus × canescens under Sodium Chloride Stress      

Abstract: Salt-induced fluxes of H+ , Na + , K + , and Ca 2+ were investigated in ectomycorrhizal (EM) associations formed by Paxillus involutus (strains MAJ and NAU) with the salt-sensitive poplar hybrid Populus 3 canescens. A scanning ion-selective electrode technique was used to measure flux profiles in non-EM roots and axenically grown EM cultures of the two P. involutus isolates to identify whether the major alterations detected in EM roots were promoted by the fungal partner. EM plants exhibited a more pronounced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
58
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 67 publications
(104 reference statements)
5
58
0
1
Order By: Relevance
“…To date, few studies have reported on the effects of mycorrhizal fungi on the acclimatization of microplants of forest trees to ex vitro conditions. A positive effect of in vitro ECM inoculation on poplar growth was previously reported for Populus tremula L. 9 Populus tremuloides Mich (Hampp et al 1996;Loewe et al 2000) and for P. 9 canescens (Gafur et al 2004;Li et al 2012;Ma et al 2014). Inoculation of microplants ex vitro with mycorrhizal fungi has been shown to improve poplar survival rate, health status, and growth post-acclimatization (Langer et al 2008).…”
Section: Introductionmentioning
confidence: 75%
See 3 more Smart Citations
“…To date, few studies have reported on the effects of mycorrhizal fungi on the acclimatization of microplants of forest trees to ex vitro conditions. A positive effect of in vitro ECM inoculation on poplar growth was previously reported for Populus tremula L. 9 Populus tremuloides Mich (Hampp et al 1996;Loewe et al 2000) and for P. 9 canescens (Gafur et al 2004;Li et al 2012;Ma et al 2014). Inoculation of microplants ex vitro with mycorrhizal fungi has been shown to improve poplar survival rate, health status, and growth post-acclimatization (Langer et al 2008).…”
Section: Introductionmentioning
confidence: 75%
“…Under natural conditions, H. crustuliniforme and P. involutus develop ECM symbiosis with a wide Laccaria laccata, and Pisolithus tinctorius) did not form ECM structures with P. deltoides roots, although they colonized extensively the growth medium (Reddy and Satyanarayana 1998). Selected strains of P. involutus used for inoculation of P. 9 canescens microplants enhanced tolerance of the poplar plants to salt stress (Langenfeld-Heyser et al 2007;Li et al 2012), drought stress (Luo et al 2009b), and cadmium toxicity (Ma et al 2014). Although Populus spp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Instead, a non-invasive micro-test technique (NMT) successfully developed by Shabala and coadjutant colleagues Garnett et al, 2001) is widely accepted due to its precise detections on the movement of plasma membrane (PM) H + -ATPase in the Na + /H + antiport according to ion kinetics in response to salt shock. Under salt stress, the pattern of short-term flux profiles of salinity ions of Na + , K + , and Cl -, has been well quantified using NMT on Arabidopsis (Shabala et al, 2005), Poplar (Sun et al, 2009), Mangrove (Lu et al, 2013), and some strains in mycorrhizal Poplar roots (Li et al, 2012;Ma et al, 2014). According to these studies, the short-term salt-induced efflux of intracellular K + was highlighted because salt impact would be intensified when K + loss is accompanied by accumulation of Na + inside the cytosol with a high level of Na + concentration in the range of 50-200 mM (Maathuis and Amtmann, 1999;Flowers and Hajibagheri, 2001;Britto et al, 2010).…”
Section: Introductionmentioning
confidence: 99%